Two new species of the flat-backed millipede genus Chonodesmus Cook, 1896 (Polydesmida, Cryptodesmidae, Cryptodesmini) from Colombia with a redescription of the type species - Reyes-Peñata, Liseth Alejandra; Romero-Rincon, Juan; Martínez-Torres, Daniela; García-Sarmiento, Martha J. (Zootaxa, 2025)
The millipede genus Chonodesmus Cook, 1896 has so far been represented in Colombia by C. alatus (Peters, 1865) and C. regularis Cook, 1896 both from Bogotá D.C. and by C. gervaisi Hoffman, 1973 from San Agustín, Huila Department. Two new species are described here: C. muisca sp. nov. from three localities in Cundinamarca Department and C. simplex sp. nov. from Parque Natural Regional Ucumarí, Risaralda Department. Chonodesmus alatus, the type species of genus, is revised, illustrated and with its lectotype is here designed. Chonodesmus regularis is considered as a nomen dubium, being based on an immature male holotype. Both C. alatus and C. regularis may prove to actually represent one and the same species, C. alatus by priority, but a clarification must be deferred pending the discovery of topotypes from Bogotá D.C.